Synthesis and Growth Mechanism of Net-like Titanate Nanowire Films via Low-temperature and Low-alkali-concentration Route - Huang, Xinwen; Liu, Zongjian (Nano-Micro Letters, 2013)
Net-like titanate nanowire films can be grown on Ti substrates by non-hydrothermal treatment of Ti foils in alkali-H2O2 aqueous solutions with a low alkali concentration of 2 M at 60–80°C. The growth mechanism of such films has been investigated by identifying the role of both H2O2 and alkali in the nanowire formation and capturing the film morphology at early growth stages. It is found that the presence of H2O2 is necessary for the nanowire growth, and sufficient amount of H2O2 is needed to produce well-shaped nanowires. The nanowire growth is also strongly dependant on the alkali used, and nanowire films are formed only when metal hydroxides which can react with TiO2 to form layer-structured titanates are chosen. Our results have also revealed that the heterogeneous deposition of titanate on Ti substrate results in the growth of titanate sheets, and the nanowire formation is via a splitting process by which each titanate sheet gradually evolves into nanowire thin layer. Based on the experimental results, a detailed mechanism is proposed for the growth of titanate nanowire films in alkali-H2O2 aqueous solutions at low temperature.